The giant, the flightless, and the iridescent: seven new endemic genera of Hawaiian leaf-roller moths (Lepidoptera: Tortricidae) - Austin, Kyhl A.; Rubinoff, Daniel (Zootaxa, 2026)
Seven new endemic genera and ten new species of Tortricidae are described from the Hawaiian Islands; all are assigned to Archipini (Tortricinae). A further eleven new combinations and one restored status are proposed. Iliahia, gen. nov. (type species: Capua flavopicta Walsingham), is described for six species which feed on the foliage of ʻiliahi (Santalum spp.; Santalaceae): Iliahia flavocincta (Walsingham), comb. nov., Iliahia flavopicta (Walsingham), comb. nov., Iliahia lilinoe, sp. nov., Iliahia pahulu, sp. nov., Iliahia santalata (Swezey), comb. nov., reinst. stat., and Iliahia xanthogona (Walsingham), comb. nov.; Nomewaimea, gen. nov. (type species: Epagoge infaustana Walsingham), is described for four species which feed on the leaves, shoots, and stems of ōpuhe (Touchardia sandwicensis; Urticaceae) and māmaki (Pipturus spp.; Urticaceae): Nomewaimea alaea, sp. nov., Nomewaimea kupenuia, sp. nov., Nomewaimea infaustana (Walsingham), comb. nov., and Nomewaimea urerana (Swezey), comb. nov.; Kumakena, gen. nov. (type species: Capua cassia Swezey), is described for Kumakena cassia (Swezey), comb. nov., which feeds on the leaves of kolomona (Senna gaudichaudii; Fabaceae); Limua, gen. nov. (type species: Archips lichenoides Walsingham), is described for four species which feed on the leaves of olopua (Notelaea sandwicensis; Oleaceae) and kōpiko (Psychotria spp.; Rubiaceae): Limua fuscoviridis (Walsingham), comb. nov., Limua lichenoides (Walsingham), comb. nov., Limua pahole, sp. nov., and Limua trochilidanus (Walsingham), comb. nov.; Paalua, gen. nov. (type species: Panaphelix asteliana Swezey), is described for three species which feed on the leaves of paʻiniu (Astelia spp.; Asteliaceae): Paalua asteliana (Swezey), comb. nov., Paalua maunaloa, sp. nov., and Paalua leleole, sp. nov.; Aipoola kaumualii, gen. nov., sp. nov., is described for a new species which feeds on the leaves of poʻolā (Claoxylon sandwicense; Euphorbiaceae); and Maneapakele, gen. nov. (type species: Maneapakele hapalua Austin & Rubinoff), is described for two species which feed in the fruits of pāpala kēpau (Ceodes spp.; Nyctaginaceae): Maneapakele hapalua, sp. nov., and Maneapakele kahaha, sp. nov. Lectotypes are designated for four species. With the exception of K. cassia and possibly I. pahulu and I. santalata, all species are believed to be single-island endemics. We assess the conservation status for all species treated. All previously described species transferred to these new genera are provided with a new diagnosis in the context of the new species. A generic key to Tortricidae in Hawaiʻi and a species checklist is provided.